Oxyresveratrol Attenuates Inflammation in Human Keratinocyte via Regulating NF-kB Signaling and Ameliorates Eczematous Lesion in DNCB-Induced Dermatitis Mice - Hung Gia Tran; Aussavashai Shuayprom; Patipark Kueanjinda; Asada Leelahavanichkul; Prapai Wongsinkongman; Siriwan Chaisomboonpan; Apiwat Tawatsin; Kriangsak Ruchusatsawat; Jongkonnee Wongpiyabovorn (MDPI AG, 2023)
Oxyresveratrol (ORV) is one of the novel antioxidants having been extensively studied in recent years. One of the main sources of ORV is Artocarpus lakoocha, which has been used in traditional medicine in Thailand for decades. However, the role of ORV in skin inflammation has not been clearly demonstrated. Therefore, we investigated the anti-inflammatory effects of ORV on dermatitis model. The effect of ORV was examined on human immortalized and primary skin cells exposed to bacterial components including peptidoglycan (PGN) and lipopolysaccharide (LPS) and 2,4-Dinitrochlorobenzene (DNCB)-induced dermatitis mouse model. PGN and LPS were used to induce inflammation on immortalized keratinocytes (HaCaT) and human epidermal keratinocytes (HEKa). We then performed MTT assay, Annexin V and PI assay, cell cycle analysis, real-time PCR, ELISA and Western blot in these in vitro models. H&E staining, immunohistochemistry (IHC) staining with CD3, CD4 and CD8 markers were used to evaluate the effects of ORV in in vivo model of skin inflammation using BALB/c mice. Pretreatment of HaCaT and HEKa cells with ORV inhibited pro-inflammatory cytokine production through inhibition of NF-κB pathway. In DNCB-induced dermatitis mouse model, ORV treatment reduced lesion severity, and skin thickness and numbers of CD3, CD4 and CD8 T cells in the sensitized skin of mice. In conclusion, it has been demonstrated that ORV treatment can ameliorate inflammation in the in vitro models of skin inflammation and in vivo models of dermatitis, suggesting a therapeutic potential of ORV for treatment of skin diseases particularly eczema.